Community Pharmacists and Their Role in Non-Communicable Disease (NCD) Management: A Critical Review of Global and Indian Evidence - Kokkula, Bharath Chandra (Indian Journal of Pharmacy Practice)
Background: Non-Communicable Diseases (NCDs) are the leading cause of morbidity and mortality globally, with India facing a rising burden. Community pharmacists, due to their accessibility and trust within communities, are well-positioned to support NCD prevention, early diagnosis, and long-term care. Aim: To critically review global and Indian evidence on the role of community pharmacists in NCD management and provide practical recommendations for their integration into India’s primary healthcare system. Materials and Methods: This narrative review draws on literature from 2000 to 2025, sourced through databases such as PubMed, Google Scholar, Scopus, and institutional reports. Priority was given to studies from Low- and Middle-Income Countries (LMICs), including India, that evaluated pharmacist-led interventions in NCD care. Results: International and Indian studies demonstrate that pharmacist-led interventions improve clinical outcomes in diabetes, hypertension, asthma, and adherence. However, despite policy frameworks like NPCDCS and Ayushman Bharat, pharmacists in India remain underutilized. Training gaps, limited recognition, and weak policy integration hinder their broader involvement. Conclusion: Community pharmacists can play a critical role in India’s NCD response if empowered through policy support, structured training, digital tools, and formal inclusion in national programs. Their integration into primary care teams could reduce the disease burden and improve long-term health system efficiency.
Keywords: Community pharmacists; Non-communicable diseases; India; Diabetes; Hypertension; NPCDCS; Pharmacy policy; Primary healthcare; Pharmacist training